Front Cover: Lifting the Spin‐Momentum Locking in Ultra‐Thin Topological Insulator Films (Adv. Quantum Technol. 11/2021). Issue 11 (8th November 2021) - Leis, Arthur; Schleenvoigt, Michael; Cherepanov, Vasily; Lüpke, Felix; Schüffelgen, Peter; Mussler, Gregor; Grützmacher, Detlev; Voigtländer, Bert; Tautz, F. Stefan
Abstract : In article number 2100083, Arthur Leis, Bert Voigtländer and co‐workers demonstrate nanoscale four‐probe measurements on atomically thin topological insulator films. For this purpose, four individual scanning tunneling microscope tips are directly contacting individual terraces on the sample surface to quantify the thickness‐dependent film conductivity. This enables the authors to detect a breakdown of spin‐momentum locking in the topological surface state as a function of the film thickness. In the few‐layer limit, this effect can realize helical edge modes along step edges with potential applications in spintronics and quantum computing.